Experimental Study on the Condensation of Steam With Air Out of the Vertical Tube Bundles - Wang, Lu; Chen, Ping; Zhou, Yi; Li, Wei; Tang, Changbing; Miao, Yifei; Meng, Zhaoming (Frontiers in Energy Research, 2018)
In this paper, experimental study was carried out in an open natural circulation loop, to figure out the condensation heat transfer characteristic on the outside of the vertical pipe tube bundle and single- tube. Condensation heat transfer coefficients have been obtained under the wall subcooling ranging from 5 to 22°C, total pressure ranging from 0.3 to 0.6 MPa and air mass fraction ranging from 0.05 to 0.65. The influence of mixed gas pressure, condensate depression of walls, and content of non-condensable gas on the condensation heat transfer performance is analyzed. Under the condition of the same air mass fraction, the condensation heat transfer coefficient increases with the increase of pressure. Also, as the air mass fraction is more than 30%, the effect of pressure will be weakened. The heat transfer features of pipe bundle and single tube is compared and studied, and an empirical correlation of the pipe bundle for the heattransfer coefficient is developed, covered all data points within 10%. According to the research results, heat transfer coefficient for pipe bundle decreases with the increase in non-condensable gas quality and wall subcooling, but increases with the increase in pressure.